HUBUNGAN ANEMIA DENGAN KEJADIAN PARTUS KALA I MEMANJANG DI PUSKESMAS ROGOTRUNAN KABUPATEN LUMAJANG - Yuniarsih, Sri Ayu; Ermawati, Iit; Sary, Yessy Nur Endah (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Prolonged parturition is one of the causes of maternal death in Indonesia, which continues to increase, reaching 1.8% in 2012. The average incidence of long labor in the world causes maternal death by 8% and in Indonesia by 9%. Pregnant women with anemic will experience a risk of bleeding due to hypotonia or atony of 20-25 percent. The contracting uterus requires energy and oxygen supplied by the blood. Low energy and oxygen supplied can cause prolonged parturition and the risk of complications in childbirth that can lead to maternal death. In Lumajang, there has been an increase in the maternal mortality rate from 97 in 2020 to 309 in 2021, where the Rogotrunan Health Center is the area with the highest maternal mortality with 8 deaths. This study aims to determine the correlation between anemia and the incidence of the prolonged first stage of labor. This research was analytical research using a retrospective method which is sourced from secondary data, namely medical records. Of the 348 mothers who gave birth, 83 mothers in labor with anemia (23.48%) were found. Of the 83 anemic mothers in labor, 49 experienced a prolonged first stage (59.1%). From the results of the Pearson product-moment test, it was known that the significance value (r) was 0.000 with a significant value (p) of 0.05. It was concluded that r <p, there is correlation between anemia and the incidence of prolonged first-stage labor. Based on the results of the study, there is correlation between anemia and the incidence of the prolonged first stage, so it is hoped that there will be prevention of anemia in pregnant women to prevent prolonged first-stage events.